Revealing the role of the benzyloxy pharmacophore in the design of a new class of monoamine oxidase‐B inhibitors. Issue 8 (13th May 2022) - Sudevan, Sachithra T.; Rangarajan, T. M.; Al‐Sehemi, Abdullah G.; Nair, Aathira S.; Koyiparambath, Vishal P.; Mathew, Bijo
Abstract: The conceptual layout of monoamine oxidase (MAO) inhibitors has been modified to explore their potential biological application in the case of neurological disorders for the time being. The current review article is an effort to display the summation of innovative conceptual prospects of MAO inhibitors and their intriguing chemistry and bioactivity. Based on this scenario, we emphasize the pivotal role of the benzyloxy moiety attached to scaffolds like oxadiazolones, indolalkylamines, safinamide, caffeine, benzofurans, α‐tetralones, β‐nitrostyrene, benzoquinones, coumarins, indoles, chromones, and chromanone analogs, while acting as an MAO inhibitor. Abstract : Monoamine oxidase (MAO) inhibitors with various structures have been explored regarding their potential biological application in the case of neurological disorders. The current review article gives an overview of new conceptual prospects of MAO inhibitors and their intriguing chemistry and bioactivity. The pivotal role of the benzyloxy moiety attached to various scaffolds is emphasized.